Impact of operational risk on corporate financial performance: a literature review - CHEGRI, Soukaina; EL BAKKOUCHI , Mounir (Revue Internationale du Chercheur, 2022)
The scandals that have occurred in the financial world, among others, have demonstrated the extent of the phenomenon of operational risk and its management. As for operational risk management, it is a process by which companies identify and evaluate the risks impacting their business, it has become important to implement an operational risk management system because performance cannot be achieved without having addressed the aspects related to operational risk management. In the world of management, performance is the ultimate result of all the efforts made by the company to achieve its objectives. In fact, operational risk has a major impact on the performance of a company, regardless of its sector of activity, because of the impact of this type of failure on the performance and stability of companies. The present contribution is an attempt to review the literature, the purpose of this article is to study the impact of operational risk management on the financial performance of companies, in order to know if risk management has a positive or negative impact on the financial performance of companies.